Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s00464-019-07270-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulator training and residents’ first laparoscopic hysterectomy: a randomized controlled trial

Abstract: Background Hysterectomy rates are decreasing in many countries, and virtual reality simulators bring new opportunities into residents' surgical education. The objective of this study was to evaluate the effect of training in laparoscopic hysterectomy module with virtual reality simulator on surgical outcomes among residents performing their first laparoscopic hysterectomy. Methods This randomized study was carried out at the Department of Obstetrics and Gynecology in Helsinki University Hospital and Hyvinkää H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The importance of video recording has been highlighted in several studies. 18,19 The assessors also scored the candidates according to an already validated global rating scale, 7,20 which was utilised as a control tool for testing the criterion validity of the proposed objective structured assessment of technical skill in temporal bone dissection. As shown in Figure 5, objective structured assessment of technical skill in temporal bone dissection consists of seven questions (scored as yes/no) and one question of overall achievement, scored from 0 to 5.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of video recording has been highlighted in several studies. 18,19 The assessors also scored the candidates according to an already validated global rating scale, 7,20 which was utilised as a control tool for testing the criterion validity of the proposed objective structured assessment of technical skill in temporal bone dissection. As shown in Figure 5, objective structured assessment of technical skill in temporal bone dissection consists of seven questions (scored as yes/no) and one question of overall achievement, scored from 0 to 5.…”
Section: Methodsmentioning
confidence: 99%
“…From the realm of gynecologic resident education, Jokinin also showcased the utility of virtual reality laparoscopic simulation with hysterectomy. Of note, while operative time did not reach statistical significance due to low number of study participants, residents who completed the intervention of the laparoscopic hysterectomy simulation performed their first live hysterectomy an average of 20 min faster ( 18 ). In another gynecologic example, Netter took training a step forward and identified that video-based self-assessment can improve surgical skills on virtual reality laparoscopic hysterectomy simulation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the requirements of the teaching plan, the teacher should identify situational cases, teaching objectives and specific teaching tasks successively. After assigning tasks to students, the teacher should not give a lecture immediately but guide the students to think independently and analyze carefully, which helps them complete the learning tasks better [5]. The main procedures and steps for implementing this method are as follows:…”
Section: Objects and Methodsmentioning
confidence: 99%